Road to Recovery - Ana C. Ruiz; Abdul Haseeb; Marcela C. Carbajal Tamez; William Baumgartner; Edison Leung; Giselli Scaini; João L. de Quevedo (The Journal of ECT, 2026)
Electroconvulsive therapy (ECT) remains a core intervention for severe, treatment-resistant depression (TRD), especially in patients with suicidality or psychosis. However, the safety and efficacy of ECT in individuals with prior epilepsy surgery, such as temporal lobectomy, are not well-established. This report presents the clinical course of a male patient in his late 30s with recurrent depression since the age of 16, chronic suicidality with prior suicide attempts, who completed a course of bifrontal ECT consisting of a 21-session index phase followed by an 11-session continuation phase. Medical history includes epilepsy, resulting in a right temporal lobectomy 14 years ago. The patient underwent 32 bifrontal ECT sessions over a period of 5 months and achieved complete symptomatic remission (PHQ-9 score: 21 to 0), functional recovery, and a subjectively reported improvement in memory and cognition, with no adverse effects. This case contributes to the limited literature supporting the use of ECT in postlobectomy populations and highlights its potential in complex neuropsychiatric presentations.